RESEARCH OF BASIC ECONOMIC KNOWLEDGE AMONG CHILDREN OF SENIOR PRESCHOOL AGE - Umnov Dmitriy Gennadievich (Galaxy International Interdisciplinary Research Journal, 2021)
The article deals with the diagnosis of the formation of elementary economic knowledge in older preschoolers. Economic knowledge of preschool children is expressed in their analytical and synthetic skills, the ability to generalize and classify, the ability to solve entertaining problems with economic content and apply the knowledge acquired in a new situation. A study was conducted in older preschoolers in pre-school education, children’s knowledge was analyzed and a statistical analysis of the results was made based on the data gathered. Based on the analysis of psychological and pedagogical point of view on an investigated problem, based on the understanding of the formation of basic economic knowledge among preschoolers as a complex, dynamic process, descriptive criteria and indicators on economic knowledge of preschool children were distinguished.